The Application of Powerpoint Media in Thematic Learning in The Second Grade of Elementary School - Uzima Candrawati (JP2D (Jurnal Penelitian Pendidikan Dasar) UNTAN, 2019)
This study aimed to adjust the predetermined theme with the theme implemented. In addition, giving interesting presentations to students, and teachers can improve the quality of human resources in the field of technology and information. This study used a qualitative approach. Data sources consisted of primary data and secondary data through procedures for collecting data with participatory observation, in-depth interviews, and documentation studies. The data analysis technique in this study used domain techniques, taxonomic techniques, compound techniques, and theme techniques. For the process of checking the validity of the data, a triangulation process was carried out to obtain accurate research results. The results of the study obtained that in thematic learning using the Lesson Plan (RPP) to achieve a basic competency set out in the Content Standards and described in the syllabus through various learning behaviors of students.